ANALISIS AKUNTABILITAS, TRANSPARANSI, DAN SUMBER DAYA MANUSIA TERHADAP PENGELOLAAN KEUANGAN DESA DEMI MEWUJUDKAN GOOD GOVERNANCE (Studi Kasus pada Pemerintah Desa Kabupaten Brebes) - Kharisma Yosi Noviana; Haryanto Haryanto (Diponegoro Journal of Accounting, 2023)
This research aims to examine the effect of accountability, transparency and human resources on village financial management in the village government in Brebes District, Central Java Province. The population of this research is 292 villages in Brebes Regency. The sampling technique used a saturated sample, with a total sample of 169 respondents, namely village administration. This study uses primary data obtained by distributing questionnaires. The data analysis method used is multiple linear regression analysis. The results of the research that has been done show that accountability does not affect village financial management, while transparency has a positive effect on village financial management.